2018
DOI: 10.1063/1.5023851
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive NO2 gas sensors using hybrid heterojunctions of multi-walled carbon nanotubes and on-chip grown SnO2 nanowires

Abstract: Hybrid heterojunction devices are designed for ultrahigh response to NO2 toxic gas. The devices were constructed by assembling multi-walled carbon nanotubes (MWCNTs) on a microelectrode chip bridged bare Pt-electrode and a Pt-electrode with pre-grown SnO2 nanowires (NWs). All heterojunction devices were realized using different types of MWCNTs, which exhibit ultrahigh response to sub-ppm NO2 gas at 50 °C operated in the reverse bias mode. The response to 1 ppm NO2 gas reaches 11300, which is about 100 times hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 31 publications
0
16
1
Order By: Relevance
“…Figure 4A is the Sn3d spectrum of the AuNPs-SnO 2 -rGO ternary nanocomposite. As can be seen from the figure, two strong peaks occur at 486.36 and 494.81 eV, attributed to the binding energy of Sn3d 3/2 and Sn3d 5/2 , respectively, indicating the SnO 2 formation (Khlayboonme and Thowladda, 2018; Nguyet et al, 2018). Figure 4B reveals the Au4f spectrum of the AuNPs-SnO 2 -rGO hybrid, confirming the Au presence in the hybrids, with significant signals at 87.6 and 83.36 eV corresponding to metallic Au (Meng et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…Figure 4A is the Sn3d spectrum of the AuNPs-SnO 2 -rGO ternary nanocomposite. As can be seen from the figure, two strong peaks occur at 486.36 and 494.81 eV, attributed to the binding energy of Sn3d 3/2 and Sn3d 5/2 , respectively, indicating the SnO 2 formation (Khlayboonme and Thowladda, 2018; Nguyet et al, 2018). Figure 4B reveals the Au4f spectrum of the AuNPs-SnO 2 -rGO hybrid, confirming the Au presence in the hybrids, with significant signals at 87.6 and 83.36 eV corresponding to metallic Au (Meng et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
“…In a typical XRR curve, for incident angles greater than the critical angle, the X-ray beam penetrates inside the film and will ensue in a characteristic oscillatory reflection pattern with a period of 2π/d called Kiessig fringes. 10 For the incident angles greater than the critical angle, the intensity of specular reflectivity (the incident and exit angles are equal) for an ideal flat surface drops off as 1=q 4 z , where the q z is the scattering vector normal to the surface. 11 Meanwhile, for a rough surface, the intensity slumps since the Debye-Waller-type factor is multiplied by the XRR intensity.…”
Section: X-ray Reflectivity (Xrr) Is a Well-established And Nondestrumentioning
confidence: 99%
“…3 As a gas sensor, SnO 2 exhibits much critical sensitivity to detect water vapor, hydrogen, and CO, CO 2 , and NO x gases. [4][5][6] The significant influence of the precursor composition (PC) on the structure and properties of the thin films by spray pyrolysis technique has already been investigated through atomic force microscopy and photoluminescence spectral analyses. 7 The surface morphology of the zinc-doped SnO 2 thin films prepared by spray pyrolysis was studied, and a reduction in surface roughness was deduced with the addition of Zn in the starting solution.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Nguyet et al [61] found that when CNTs are mixed with SnO 2 nanowires, instead of SnO 2 film like in Ref. [59] or SnO 2 powders as in Ref.…”
Section: Carbon Nanotube-based Gas Sensorsmentioning
confidence: 99%